Photographic atlas of fish otoliths of the Northwest Atlantic Ocean - Campana, Steven E., 1955- (Canadian special publication of fisheries and aquatic sciences, 2004)
The shape of fish otoliths is highly species specific. Since otoliths resist degradation better than most other tissues, the shape and size of preserved or undigested otoliths recovered from fossilized sediments, native middens, and the stomachs and droppings of fish predators can be used to reconstruct the species composition of the diet or fish assemblage. This photographic atlas presents light and (or) scanning electron micrographs of 580 pairs of sagittal otoliths representing 288 species, 97 families, and 27 orders of fish from the northwest Atlantic.